The relationship between economic preferences and psychological personality measures - Anke Becker; Thomas Deckers; Thomas Dohmen; Armin Falk; Fabian Kosse (Center for Economic Studies and ifo Institute (CESifo), 2012)
Although both economists and psychologists seek to identify determinants of heterogeneity in behavior, they use different concepts to capture them. In this review we first analyze the extent to which economic preferences and psychological concepts of personality - such as the Big Five and locus of control - are related. We analyze data from incentivized laboratory experiments and representative samples and find only low degrees of association between economic preferences and personality. We then regress life outcomes - such as labor market success, health status and life satisfaction - simultaneously on preference and personality measures. The analysis reveals that the two concepts are rather complementary when it comes to explaining heterogeneity in important life outcomes and behavior.
Keywords: C91; D01; D80; D90; I00; J30; J62; 330; risk preference; time preference; social preferences; locus of control; Big Five